The Impact of Immigration on Firms and Workers: Insights from the H-1B Lottery - Parag Mahajan; Nicolas Morales; Kevin Y. Shih; Mingyu Chen; Agostina Brinatti (Institute of Labor Economics (IZA), 2024)
We study how random variation in the availability of highly educated, foreign-born workers impacts firm performance and recruitment behavior. We combine two rich data sources: 1) administrative employer-employee matched data from the US Census Bureau; and 2) firmlevel information on the first large-scale H-1B visa lottery in 2007. Using an event-study approach, we find that lottery wins lead to increases in firm hiring of college-educated, immigrant labor along with increases in scale and survival. These effects are stronger for small, skill-intensive, and high-productivity firms that participate in the lottery. We do not find evidence for displacement of native-born, college-educated workers at the firm level, on net. However, this result masks dynamics among more specific subgroups of incumbents that we further elucidate.
Keywords: F22; J61; 330; immigration; firm dynamics; productivity; H-1B visa; high-skilled migration